Baby face Princess - Dahl, Michael; Ho, Jannie (North Mankato, MN Capstone Young Readers, a CApstone imprint, 2015)
In simple rhyming text, and when a photo of a baby is inserted, the child will appear to be a princess through die-cut holes
A gift from book Africa
English stories
1 2 13 15
Keywords: Infants -- Juvenile fiction; Princesses -- Juvenile fiction